2013
DOI: 10.1111/all.12186
|View full text |Cite
|
Sign up to set email alerts
|

Risk of angioedema following invasive or surgical procedures in HAE type I and II – the natural history

Abstract: BackgroundHereditary angioedema (HAE), caused by deficiency in C1-inhibitor (C1-INH), leads to unpredictable edema of subcutaneous tissues with potentially fatal complications. As surgery can be a trigger for edema episodes, current guidelines recommend preoperative prophylaxis with C1-INH or attenuated androgens in patients with HAE undergoing surgery. However, the risk of an HAE attack in patients without prophylaxis has not been quantified.ObjectivesThis analysis examined rates of perioperative edema in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 26 publications
0
59
0
11
Order By: Relevance
“…Moreover, a single patient could present or not present AE after the same procedure [70][71][72]. There are no controlled studies that assess STP efficacy; current available data come from observational studies: The risk of perioperative AE without STP (not taking into account dental procedures) is 6-31% [73].…”
Section: Recombinant Human C1 Inhibitormentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a single patient could present or not present AE after the same procedure [70][71][72]. There are no controlled studies that assess STP efficacy; current available data come from observational studies: The risk of perioperative AE without STP (not taking into account dental procedures) is 6-31% [73].…”
Section: Recombinant Human C1 Inhibitormentioning
confidence: 99%
“…There is no increased risk related to the procedure location or surgical area size [73]. The prevalence of AE attacks after dental procedures performed without STP varies from 5 to 37% of patients [71][72][73]. Farkas et al observed that 40% of the patients who had not performed STP developed AE post-procedures, when assessing all the interventions as a whole [74].…”
Section: Recombinant Human C1 Inhibitormentioning
confidence: 99%
See 2 more Smart Citations
“…
ВВЕДЕНИЕБоль в животе -одна из наиболее частых причин обращения за помощью к врачу во всем мире [1,2]. Причины боли в животе многочисленны, но в первую очередь необходимо исключить хирургическую патоло-гию, что особенно актуально у детей.
…”
unclassified